2020
DOI: 10.3390/ijms21051828
|View full text |Cite
|
Sign up to set email alerts
|

JA-Ile-Macrolactone 5b Induces Tea Plant (Camellia sinensis) Resistance to Both Herbivore Ectropis obliqua and Pathogen Colletotrichum camelliae

Abstract: Jasmonates (JAs), the group of lipid-derived hormones, were found to control the defense responses in a myriad of plants. Meaningfully, the macrolactones of 12-hydroxy jasmonate isoleucine (12OH-JA-Ile) were reported to induce the defensive response of wild tobacco. However, little to nothing has been known about the elicitation effect of JA-Ile-macrolactones on woody plants to harmful organisms, let alone its underlying mechanisms. Here, we first optimized the synthetic routine using mild toxic reagent isobut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Ca 2+ , MPKs, WRKYs and JA are well‐known regulators of plant resistance to chewing herbivores (Erb & Reymond, 2019; Kanchiswamy et al, 2010; Liu, Li, Xu, Wang, & Lou, 2018; Vadassery et al, 2012; Wu, Hettenhausen, Meldau, & Baldwin, 2007). Flavonoids, phenolamides, phenolic acids, and purine alkaloids are feeding deterrents (Lin et al, 2020; Onkokesung et al, 2014; Onyilagha et al, 2012; Sharma & Sohal, 2013; Wang, Yu, et al, 2020). As indole primes these signalling components and metabolites, and as Ca 2+ and JA inhibition results in the disappearance of the indole‐dependent increase in defence and resistance, we propose that indole enhances tea resistance by enhancing early defence signalling, JA biosynthesis and defensive metabolite accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2+ , MPKs, WRKYs and JA are well‐known regulators of plant resistance to chewing herbivores (Erb & Reymond, 2019; Kanchiswamy et al, 2010; Liu, Li, Xu, Wang, & Lou, 2018; Vadassery et al, 2012; Wu, Hettenhausen, Meldau, & Baldwin, 2007). Flavonoids, phenolamides, phenolic acids, and purine alkaloids are feeding deterrents (Lin et al, 2020; Onkokesung et al, 2014; Onyilagha et al, 2012; Sharma & Sohal, 2013; Wang, Yu, et al, 2020). As indole primes these signalling components and metabolites, and as Ca 2+ and JA inhibition results in the disappearance of the indole‐dependent increase in defence and resistance, we propose that indole enhances tea resistance by enhancing early defence signalling, JA biosynthesis and defensive metabolite accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of desirable traits of this cultivar are characterized (Wang et al, 2020). The tea plants were maintained in plastic pots (15 cm depth and 14 cm diameter) with commercial potting soil, and grown in the greenhouse with regular fertilizer and water management as described previously (Lin et al, 2020). Two‐year‐old healthy tea plants with uniform height and width (28 cm height and 25 cm width) were selected and transferred to a controlled environment chamber (26 ± 2°C, 70–80% relative humidity, 12:12 hr light/dark) 3 days before the start of the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing research has demonstrated that the members of the TIFY gene family, especially members of the JAZ subfamily, play multiple roles in different plant developmental processes and the process of defense against biotic and abiotic stresses [1,8,10,11,13,31]. As evergreen plants, tea plants are frequently challenged by abiotic and biotic stresses, but information on the TIFY gene family is lacking, which hampers the research investigating resistance mechanisms [27,28,31]. The chromosome-level genomic sequence of the tea plant has been recently released, and the extensive annotated information provided in the tea genome provides fundamental material for comprehensive analysis of the CsTIFY family [32].…”
Section: Discussionmentioning
confidence: 99%
“…The tea plant Camellia sinensis (L.) O. Kuntze is an economically valuable woody plant, and this evergreen crop is continuously challenged by a wide variety of biotic stresses, such as the leaf-feeding pest Ectropis obliqua and the dominant leaf fungi bacterial Colletotrichum camelliae [27][28][29]. Previous studies based on transcriptomic strategies indicated that JAZ subfamily genes were involved in the interactions between the tea plant and biotic stresses [30].…”
Section: Introductionmentioning
confidence: 99%